Unusual polymorphs of rac-3-phenylpyrrolidine-2, 5-dione with Z′ = 1, 2, and 3. Issue 44 (23rd October 2019) - Timofeeva, Tatiana V.; Sena, Victoria; Averkiev, Boris B.; Bejagam, Shabari N.; Usman, Muhammad; Krivoshein, Arcadius V.
Abstract : We report two new polymorphs of rac -3-phenylpyrrolidine-2, 5-dione and discuss the structural aspects of variable- Z ′ polymorphism in this compound. Abstract : 3-Phenylpyrrolidine-2, 5-dione (PPD) is the pharmacologically relevant metabolite of the clinically used antiepileptic drug phensuximide. In 1973, Gy. Argay and A. Kálmán, Acta Crystallogr., Sect. B: Struct. Crystallogr. Cryst. Chem., 1973, 29, 636–638 described an orthorhombic modification (polymorph I) of rac -PPD with one molecule in the asymmetric unit ( Pna 21 ; Z ′ = 1) and mentioned the existence of another, monoclinic modification (polymorph II). By varying the crystallization conditions, we were able to obtain diffraction-quality crystals of the monoclinic polymorph II ( P 21 / c ; Z ′ = 2) and of novel triclinic polymorph III ( P 1̄; Z ′ = 3). In this paper, we report a detailed structural comparison of these variable- Z ′ polymorphs of rac -PPD. We found a remarkable diversity of intermolecular interactions (medium-strength N–H⋯O hydrogen bonds, weak C–H⋯O hydrogen bonds, carbonyl–carbonyl interactions, edge-to-face aromatic–aromatic interactions). We also explored the relative stability of these polymorphs (as indicated by crystal lattice energies and thermal analysis data). Our results are expected to aid in developing a better understanding of solid-state structure of cyclic imide-based antiepileptic drugs.